Farmer Mentoring in Determining Fertilization Dosage of Corn Plants (Zea Mays L.) Using Soil Test Equipment - Johanes Amirrullah; Yanter Hutapea; NPS Ratmini; Agung Prabowo (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2020)
Amirrullah J, Hutapea Y, Ratmini NPS, Prabowo A. 2020. Farmer mentoring in determining fertilization dosage of corn plants (Zea mays L.) using soil test equipment. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands 9(1): 102-108.Balanced fertilization is very important to do in marginal soils. The constraints in the use of marginal soils are physical, chemical and biological soil characteristics which do not support planting growth. Determination of fertilizer dosage for corn commodity in one region can be different depending on the available nutrient content that testing needs to be carried out. This study aimed to mentor farmers in taking appropriate soil samples and determined fertilizer doses according to location specifications and application of fertilizers on target using the Dry Soil Test Kit (Perangkat Uji Tanah Kering). This activity was carried out in Fajar Jaya Village, Ogan Komering Ulu District in February 2019.Â The results of the soil analysis of the location used as a demonstration plot derived from the results of low soil fertility analysis with soil acidity at pH 4-5 with acid crystals, moderate P, K and C-organic nutrients were relatively low. The recommended fertilizer is as follows: urea 325 kg/ha given 3 times, one-third the dose, carried out 1 MST, 4 MST and 6 MST; TSP 200 kg/ha; KCl 125 kg/ha; 5,000 kg/ha of compost and 1,000 kg/ha of lime stocked during tillage 1 week before planting. Fertilization application method applied by farmers is not in accordance with the recommendations; consequently, it is necessary to fertilize to increase nutrient content.